Analysis and Legal Implications of the Constitutional Court's Decision on the Determination of the Age Limit for Presidential and Vice Presidential Candidates - Santoso Budi Nursal Umar; Waluyo Slamet Pradoto (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2025)
This research discusses the Constitutional Court Decision Number 90/PUU-XXI/2023 regarding the minimum age requirement for presidential and vice-presidential candidates as stipulated in Article 169 letter q of Law Number 7 of 2017 concerning General Elections. In that decision, the Constitutional Court ruled that the age limit of 40 years remains in effect, but with an exception for candidates who are not yet 40 years old but have previously or are currently serving as regional heads. This research employs a normative juridical method with legislative and conceptual approaches, analyzing primary legal materials such as the 1945 Constitution, Election Law, and Constitutional Court decisions, supported by secondary legal materials from academic literature and journals. The research findings indicate that the Constitutional Court's considerations are based on the principles of citizens' constitutional rights, open legal policy, and the idea of leadership experience as an alternative age requirement. This decision has positive implications, including opportunities for leadership regeneration and increased political participation by young people, but it also draws criticism for its potential to discriminate against non-regional leaders and create political suspicion. Therefore, a revision of the Election Law is needed to clarify the legal norms resulting from the Constitutional Court's decision so that it does not lead to multiple interpretations and maintains the principle of equality. This research concludes that the Constitutional Court's decision is an opportunity to strengthen democracy, but also a challenge in ensuring constitutional justice in Indonesia.